Soviet Everyday Realities – Strategies for Survival at Ideological Crossroads - Baločkaitė, Rasa (Sociologija. Mintis ir veiksmas, 2017)
Here in this paper, theoretical premises of subaltern studies, post-colonialism and pop-culture studies are applied for analysing Soviet popular consciousness and Soviet subjectivities. The research is based on the theoretical principles of subaltern studies, i.e., the ability of human consciousness to transform, appropriate and “consume” the dominant structures of meaning for individual purposes. The primary focus of this research is the “silent majority”, people who have not been either political activists or opponents of the regime. It is explored, on the basis of multiple interviews, how ideologies operate at the level of everyday life, how people perceive and interpret both official Soviet ideology and traditional pro-catholic upbringing. Particular aspects addressed in this article are the official Soviet and traditional religious holidays, church attendance and membership in official Soviet organisations, memories of the independence period, oral histories about deportations and informal knowledge about better living in the “West” as opposed to official Soviet propaganda and historiography.
Keywords: late socialism; everyday life; popular consciousness; ideology; Lithuania